A Case Reports On Bilateral Diffuse Cystic Lung Disease (Pulmonary Langerhans’ Cell Histiocytosis) - Shaik, Faizan Ali; Kasu, Snehitha; Jonnadula, Kedareswari; Ganjala, Hemalatha; Manchikanti, Hima Sathwika; Kota, Sandhya; Valaparla, Ramya (Journal of Pharmacy Practice and Community Medicine, 2026)
Diffuse Cystic Lung Disease (DCLD) is an uncommon and complex condition marked by the presence of numerous air-filled cysts scattered throughout the lung tissue. This case report discusses about a 67-year-old man who came to the hospital with symptoms including nausea, vomiting, fever, persistent cough, and chest discomfort. His medical background was notable for rheumatoid arthritis, Hypothyroidism, Cholelithiasis, and Grade I Fatty Liver Infiltration, along with a history of undergoing coronary artery angiography. Imaging studies revealed a collapse and consolidation in the lower lobe of the left lung, alongside multiple cysts in both lungs and areas of ground-glass opacity. Blood tests indicated signs of inflammation and abnormalities in hematological and liver function parameters. Based on the clinical and radiological findings, a final diagnosis of bilateral DCLD Pulmonary langerhans cell histiocytosis, was made. The patient was managed with bronchodilators, corticosteroids, NSAID’s, analgesics, and antiemetics. This case underscores the diagnostic complexity and therapeutic challenges of DCLD, emphasizing the urgent need for more research to enhance early detection and improve treatment outcomes.
Keywords: Diffuse cystic lung disease; Lung cysts; Collapse consolidation; Diagnosis; Treatment; challenges